RITUAL TABUIK DALAM KRIYA SENI RELIEF KAYU - YAHDIS SABIL, Drs. Syafril R, M.Sn, Drs. Irwan, M.Sn (Serupa The Journal of Art Education, 2014)
Ritual Tabuik resembling every year at date 1 Muharam Hijriyah by some fases. The fases is take the soil, cut the banana stem, maratadai, mahatam, arack the finger, arrack sorban, tabuik naiak pangkek, ma-oyak tabuik and to throw a way the tabuik in the sea. The finally purpose the last work is : (a) to gape the ritual tabuik in Pariaman form craft the art work relief with used wood media, (b) ti grow creativitas and a good appreciation in labour, (c) to more reference in the work art by relief art wood. Some process to realize the last work used some fases that is : the first, planning, to gate art ideas from reference a bout tabuik Pariaman from some media and direct survey to place ritual tabuik. The second, elaboration, to analize data. The third, sintecis, to arrange schedule work. The forth, to planned the sketsa. The fifth, to execution be art work relief. The title this work is Ritual Tabuik dalam Kriya seni Relief Kayu, among others are: Make tabuik 1, Make tabuik 2 Take the soil, Take the banana stem, Ma-oyak tabuik, to throw a way the tabuik.Kata kunci: ritual tabuik, relief kayu